Library and knowledge staff in England share similar perceptions of the roles and personal characteristics of the clinical librarian. (23rd March 2021) - Rudd, Sarah; Harding, Sam
Abstract: Introduction: Indications on the development of the health library and knowledge workforce (LKS) in England suggest that more staff may need to shift into clinical librarian (CL) roles. Anecdotal evidence suggested that CL roles have changed recently. Objectives: To examine perceptions of CL tasks and required personal characteristics of CLs, amongst both practising CLs and other LKS staff in England. Methods: An online survey was followed by descriptive statistical and content analysis to identify any differences in perceptions between the CL and non‐CL staff groups. Results: Response rate: 10% (123/1181). Both staff groups identified literature searching as the top core task and agreed on the main CL roles. Perceptions on the necessary personal characteristics were also similar. Ranking differed for a few tasks: non‐CL staff may ascribe more importance to some tasks (evidence synthesis, critical appraisal training and attending ward rounds/team meetings) than the CL staff state. CLs spent more time on staff management, and less time on study skills training than non‐CL staff perceived. Discussion: Results indicated that CL roles are continuing to develop, but that CLs are more integrated into library administration than some non‐CL staff believe. Conclusion: Shared perceptions around CL roles should help workforce development.